Strategi manajemen risiko terintegrasi pada lembaga keuangan syariah: Dari operasional bagi hasil hingga mitigasi risiko siber di era digital - Andiani, Alycia Afina (Maliki Interdisciplinary Journal, 2026)
The development of the Islamic financial sector in Indonesia currently faces two major challenges: meeting sharia compliance in conventional products and adapting to technological risks in the digital era. This study aims to examine the integration of risk management in Islamic financial institutions, encompassing aspects of financing operations, financial performance, and information technology risk mitigation. The method used is descriptive qualitative and literature review, analyzing four main pillars: the implementation of the profit-sharing principle (mudharabah and musyarakah), the application of risk management in Islamic fintech services, the impact of risk variables (CAR, BOPO, NPF) on profitability (ROA), and cyber threat mitigation strategies based on the case of Bank Syariah Indonesia (BSI) in 2023. The analysis results show that despite the implementation of the profit-sharing principle, public understanding and human resource quality remain major obstacles. On the other hand, digitalization through fintech provides easy access but widens the cyber risk gap, which can threaten the stability of financial performance and customer trust. The study's findings emphasize that effective risk management must be holistic, focusing not only on healthy financial ratios (reducing BOPO and NPF) but also on strengthening IT security infrastructure and Sharia literacy education. This article concludes that the future resilience of Islamic financial institutions depends heavily on the synergy between strict Sharia compliance and robust cyber defense systems.